1990
DOI: 10.1111/j.1600-0528.1990.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorosis and dental caries in 6–8‐year‐old children in a 5 ppm fluoride area

Abstract: Fluorosis levels and caries prevalence were evaluated in 152 children aged 6-8 yr residing from birth in an area with 5 ppm fluoride in the drinking water. Sixty-two of the subjects had mild fluorosis in both primary and permanent dentition, 31 were defined as moderate, and 4 cases had no signs of fluorosis; 14 cases had a more severe fluorosis level in the primary dentition as compared to 41 cases in which fluorosis was more severe in the permanent dentition. More primary dentitions were free of fluorosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
3
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
(25 reference statements)
0
10
3
6
Order By: Relevance
“…Gender differences were observed in the prevalence of fluorosis in this study with males being more commonly affected compared to females at an OR of 1.53, these findings are in contrast to the reported findings [24,25] while another study [26] has reported that variable gender did not affect the occurrence of dental fluorosis. In this study it was observed that rural population was at a significantly higher risk of dental fluorosis compared to their urban counterparts.…”
Section: Children With Fluorosiscontrasting
confidence: 56%
“…Gender differences were observed in the prevalence of fluorosis in this study with males being more commonly affected compared to females at an OR of 1.53, these findings are in contrast to the reported findings [24,25] while another study [26] has reported that variable gender did not affect the occurrence of dental fluorosis. In this study it was observed that rural population was at a significantly higher risk of dental fluorosis compared to their urban counterparts.…”
Section: Children With Fluorosiscontrasting
confidence: 56%
“…39 As the primary dentition is exfoliated, fluorosis in deciduous teeth is seen to be of little importance. However, Mann et al 40 found that occurrence of primary tooth fluorosis was closely associated with fluorosis in the permanent dentition. Milsom et al 41 reported that children with fluorosis of their primary second molars were 1.86 times as likely to develop fluorosis in their permanent incisors than those with no primary molar fluorosis.…”
Section: Prevalence Of Enamel Fluorosismentioning
confidence: 97%
“…Similar to counterintuitive histological changes in bone, the macroscopic appearance of increasing degrees of dental fluorosis was directly correlated to the degree of subsurface porosity [57]. Despite such histological changes suggesting that tooth decay prevalence may be higher among children with fluorosis, research findings have been mixed [58, 59]. There is no safe limit for fluoride ingestion in relation to dental fluorosis, but fluoridated levels exceeding 0.3 ppm have been associated with teeth mottling and discolouration [30].…”
Section: Adverse Impacts Of Fluoride Ingestion On Human Healthmentioning
confidence: 99%